Sei sulla pagina 1di 4

1.

f ' ( x )=x 6 sin x +5 x5 cosx

2. Let u=3sin ( x )v=1+cos ( x )

u' =3 cos ( x ) v ' =sin ( x )


u ' vv ' u
f ' ( x )=
v2
2
3 cos ( x ) ( 1+cosx )3 sin ( x)
f ' ( x )=
( 1+cosx )2

3 cos ( 2 ) ( 1+ cos ( 2 ) )3 sin2 (2)


f ' ( 2 )= 2
( 1+cos ( 2 ) )

3. a = 2 b=-6

4. First, we simplify the equation by simplifying the xcoefficients ( power of x )

13
3
f ( x )=7 x 2 7
x2
13 7
2 2
f ( x )=7 x 3 x
11 5
' 118 2 21 2
f ( x )= x x
2 2

5. Let u = 5x 4 du = 5 dx

5
Hence y=
u

dy
=5 ln ( u)
du
By chain rule
dy
du
dy du
=
dx dx
dy
=5 ln (u )5
dx
dy
=25 ln (5 x4)
dx

1. By trigonometric properties, we know 2 sin ( x ) cos ( x )=sin ( 2 x )


Hence , f ( x ) =4 xsin ( 2 x )

By using product rule , f ' ( x )=4 sin ( 2 x )8 xcos(2 x)


3 pi
Substituting x=
2

f' ( 32pi )=4 sin ( 3 pi) 12 picos ( 3 pi )


12 pi

2. Let u=tan ( x )5 v=sec ( x )

u' =sec 2 ( x ) v ' =sec ( x ) tan ( x )


sec ( x ) ( tan ( x )5 )tan 2 ( x ) sec ( x)
f ' ( x )=
sec 2 ( x )

' sec ( 2 ) ( tan ( 2 )5 )tan 2 ( 2 ) sec (2)


f ( 2 )=
sec 2 ( 2 )
0.17343

3 sin ( x )
3. f ( x )=
3+cos ( x )
Let u=3sin ( x ) v=3+ cos ( x )

u' =3 cos ( x ) v '=sin ( x )


2
3 ( 3+cos ( x ) ) cos ( x )3 sin (x )
f ( x )= 2
( 3+cos ( x ) )

4. f ( x )=9 x ( sin ( x ) +cos ( x ) )


f ( x )=9 xsin ( x ) + 9 xcos ( x )

f ' ( x )=9 sin ( x )+ 9 xcos ( x )+ 9 cos ( x )9 xsin ( x )

f'( pi4 )=9 sin ( pi4 )+9( pi4 )cos ( pi4 )+ 9 cos( pi4 )9( pi4 ) sin ( pi4 )
pi pi
9 ( ) 2 9 ( ) 2
9 ( 2 ) 4 9 ( 2 ) 4
+ +
2 2 2 2
9 (2)

'
5. h (t )=cos ( t ) tsin ( t ) +cos ( t )

1. f ( x )=4 x +5 g ( x )=4 x +5 Hence, h' ( 0 )=1

2. f ( x )=2 x 2+ x +1 f ' ( x )=4 x +1=9


3 x 49 x 2 +14
3. Simplify the equation getting f ( x )=
x 2 +4
4 2 2
Let u=3 x 9 x +14 v=x + 4
u' =12 x3 18 x v ' =2 x

' ( x2 + 4 ) ( 12 x 218 x ) ( 3 x 49 x 2 +14 ) ( 2 x )


f ( x )= 2
( x 2+ 4 )
29
f ' ( 2 )=
8

4. Let u=e x v=x 2+3


' x '
u =e v =2 x
( x2 +3 ) e x 2 x (e x )
f ' ( x )=
x 2+3
e
f ( 1 )=
2
3
4
5. f ( x )=3 x 15 x
1
' 9
f ( x )= x 3 15
4
9 23
f ' ( 2 )=
2
3
' 9
f ( 4 )= x 4
4